Family (oikos) Evangelism for reaching forward caste Hindus in India - Fowlkes, D. W. (Verbum et ecclesia, 2006)
This article acknowledges the need for Church Planting Movements among the unreached peoples of India. Of particular concern to this study is the application of Church Planting Movement strategy to forward caste Hindus of India. It is shown that evangelizing households (family or "oikos" evangelism) is a New Testament strategy and the most appropriate strategy for reaching forward caste Hindus. It is concluded that Christian disciples remaining within Hindu culture and familial systems hold the potential for the most indigenous approach to evangelizing forward caste Hindus.